A question best addressed in moderation: Religious affiliation and religious/spiritual importance predicting alcohol consumption in Canadians - David Speed; Allyson Lamont; Emily Earle; Stanford Yang (PLoS ONE, 2026)
One of the strongest findings in the religion/spirituality and health literature addresses the consumption of alcohol: higher levels of religion/spirituality are associated with a greater degree of abstention from, or reduced consumption of, alcohol. However, much of the existing literature assumes the measurement of religious/spiritual importance is independent of the measurement of religious affiliation. Such an assumption has led to a misestimation of the relationship between religion/spirituality and alcohol consumption. Using data from Cycle 30 of the Canadian General Social Survey ( N > 10,000), we investigated whether religious affiliation moderated the relationship between religious/spiritual importance and alcohol consumption. We compared Atheists to 19 other religious groups, with the general expectation that Atheists would report greater alcohol use. In terms of complete alcohol abstention, Protestants who rated religious/spiritual values as very important were more likely to abstain from alcohol completely, while Catholics who rated religious/spiritual values as less important were less likely to abstain from alcohol completely (relative to Atheists). When examining the frequency of alcohol consumption, Atheists were more likely to report higher frequency of alcohol consumption relative to several religious affiliations who also reported higher religious/spiritual importance. Generally, Atheists were statistically similar to religious groups reporting low-to-moderate levels of religious/spiritual importance. The current results suggest that statistical moderation is advantageous in exploring this relationship, and in the literature tying religion/spirituality to alcohol consumption.